Peranan Dongeng Interaktif Dalam Edukasi Pengelolaan Sampah Pada Anak Usia Dini - Ratnasariningsih, Julianti; Matin, Ahmad Ghilman; Efendi, Risma Yulianti Mulyani; Siregar, Maria Romauli Karunia BR (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Waste is one of the major problems in Indonesia, with most of it not managed properly, resulting in serious environmental impacts. Education about waste management from an early age is considered important to build environmental awareness. This study was conducted at At-Taqwa Kindergarten to see how interactive storytelling helps young children learn about waste management. This study used a qualitative descriptive approach, and also involved observations during interactive storytelling activities, interviews with children, teachers, and teaching teams, and documentation. The results showed that interactive storytelling is effective in helping children learn about waste management, such as sorting waste according to type, and becoming more concerned about the environment. Interactive storytelling, which involves children in the story through active participation and several learning media, creates a fun learning atmosphere and encourages imagination and deep understanding. These findings provide significant contributions for educators, parents, and educational institutions in designing innovative and effective learning methods related to waste management.